Analisis Penyebab Kerusakan Mesin Diesel pada Generator Set untuk Tindakan Perawatan di Kapal Tanker MT. Sea Serenity - Zega, Toniman; Afdal, Afdal; Abu, Risal; Mukhnizar, Mukhnizar; Azman, Azmil (Fakultas Teknik UMRI, 2024)
The generator set on the ship has the function of supplying electrical power needs. MT Tanker Ship. Sea Serenity is one of the ships that delivers goods between islands. In operation, the diesel generator engine on the MT. Sea Serenity sometimes experiences problems resulting in blackouts. This research aims to determine the factors that cause damage as well as appropriate maintenance actions and the method used is trouble shooting. Based on the research results, it is found that the causes of damage are: Engine knock, engine exhaust smoke, problems with the injection pump, worn plunger, damage to delivery valve seat, injection nozzle interference, valve opening pressure too low, engine output unstable, worn piston rings. Maintenance carried out: Injection timing must be adjusted according to ignition sequence, set injection timing, replace plunger and delivery valve seat, set valve opening pressure, replace spring, and clean injection orifice. On unstable engine output, the control rack stroke must be checked. Perform regular oil changes and regular tune ups